Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 41 A (Human Rights and Humanitarian Law - Book Archive pre-2000., 1999)
The first application to the European Commission of Human Rights was received in 1955. In over forty years, the Commission has registered more than 40 000 applications. Its published decisions run to around 150 volumes - 46 in the Collection of decisions (1960 to 1974) and nearly 100 in Decisions and reports (1975 onwards). From this mass of case-law, the authors have distilled the essential elements to produce a one-volume guide to the jurisprudence of the Convention and its protocols. In an article-by-article approach focused on the Court's case-law, they present key, passages from the judgments relevant to each article, putting them in context with their own commentary. The arrangement by article, the extensive extracts from the case-law, the detailed table of contents, and the index give the reader different ways of approaching the book, making it a useful tool for both the newcomer to Convention law and the more experienced researcher. La première requête transmise à la Commission européenne des Droits de l'Homme date de 1955. En quelque quarante ans, la Commission en a enregistré plus de 40 000. La publication de ses décisions représente environ 150 volumes: 46 Recueils des décisions, couvrant les années 1960 à 1974, et, par la suite, près de 100 volumes de Décisions et rapports. Les auteurs du présent ouvrage ont extrait l'essentiel de cette vaste jurisprudence et l'ont rassemb1é en un volume unique, présentant, pour chaque article de la Convention, les passages clés d'arrêts de la Cour et de certaines décisions de la Commission, assortis de leurs commentaires. La présentation par article de la Convention, les amples extraits de la jurisprudence, la table des matières détaillée et l'index donnent au lecteur différentes voies d'accès à cet ouvrage, outil indispensable tant pour le néophyte que pour le spécialiste plus expérimenté de la Convention.